2010
DOI: 10.1590/s0031-10492010001000001
|View full text |Cite
|
Sign up to set email alerts
|

Diet, microhabitat use, and thermal preferences of Ptychoglossus bicolor (Squamata: Gymnophthalmidae) in an organic coffee shade plantation in Colombia

Abstract: Ptychoglossus bicolor is a small gymnophthalmid lizard distributed in the Magdalena

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…By comparing our results with several similar works with gymnophthalmid lizards we can argue for some degree of historical conservatism, at least regarding D. nordestina and Ptychoglossus bicolor (Werner, 1916) (ANAYA-ROJAS et al 2010), Micrablepharus maximilianii (Reinhardt & Lütken, 1862), and Vanzosaura rubricauda (Boulenger, 1902) (D.C.P.S. Aquino, unpubl.…”
Section: Discussionsupporting
confidence: 59%
“…By comparing our results with several similar works with gymnophthalmid lizards we can argue for some degree of historical conservatism, at least regarding D. nordestina and Ptychoglossus bicolor (Werner, 1916) (ANAYA-ROJAS et al 2010), Micrablepharus maximilianii (Reinhardt & Lütken, 1862), and Vanzosaura rubricauda (Boulenger, 1902) (D.C.P.S. Aquino, unpubl.…”
Section: Discussionsupporting
confidence: 59%
“…Anaya-Rojas et al (2010) studied the diet of Ptychoglossus bicolor and observed 11 prey types in its diet, which was mainly composed of isopods. The high proportion of Isoptera in the diet of Anotosaura vanzolinia is indicative of opportunistic behavior, as there were a large number of nests of these organisms in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Por tales motivos, se sugiere que la variación observada respecto al volumen del contenido estomacal y frecuencia de consumo, es producto de la disponibilidad diferencial de presas en los distintos sitios de captura y no depende de las épocas de mayor o menor precipitación en el área de estudio. Al parecer H. frenatus en el área de estudio encuentra recursos alimentarios durante todo el año en cantidades que no fluctúan significativamente, como ha sido registrado para otras especies de lagartos en zonas tropicales (Rocha & Anjos, 2007;Anaya-Rojas et al, 2010;Caicedo-Portilla et al, 2010).…”
Section: Dietaunclassified